The career of life - Knickerbocker, Maude Ethel (My University, 1893)
Introduction: Every member of the human family, being the masterpiece of a great workman, is endowed with the fundamental, and intellectual development which characterize him from all other individuals. What influence he is to wield in this world, what his ability to control, what will be the character of his usefulness to mankind, must depend largely upon the outgrowth of these endowments.
Citation: Knickerbocker, Maude Ethel. The career of life. Senior thesis, Kansas State Agricultural College, 1893.
Morse Department of Special Collections
Keywords: Family; Workman; Mankind; Theses; Manuscripts (documents)